MRE11 and EXO1 nucleases degrade reversed forks and elicit MUS81-dependent fork rescue in BRCA2-deficient cells. Issue 1 (December 2017) - Lemaçon, Delphine; Jackson, Jessica; Quinet, Annabel; Brickner, Joshua; Li, Shan; Yazinski, Stephanie; You, Zhongsheng; Ira, Grzegorz; Zou, Lee; Mosammaparast, Nima; Vindigni, Alessandro
Abstract The breast cancer susceptibility proteins BRCA1 and BRCA2 have emerged as key stabilizing factors for the maintenance of replication fork integrity following replication stress. In their absence, stalled replication forks are extensively degraded by the MRE11 nuclease, leading to chemotherapeutic sensitivity. Here we report that BRCA proteins prevent nucleolytic degradation by protecting replication forks that have undergone fork reversal upon drug treatment. The unprotected regressed arms of reversed forks are the entry point for MRE11 in BRCA-deficient cells. The CtIP protein initiates MRE11-dependent degradation, which is extended by the EXO1 nuclease. Next, we show that the initial limited resection of the regressed arms establishes the substrate for MUS81 in BRCA2-deficient cells. In turn, MUS81 cleavage of regressed forks with a ssDNA tail promotes POLD3-dependent fork rescue. We propose that targeting this pathway may represent a new strategy to modulate BRCA2-deficient cancer cell response to chemotherapeutics that cause fork degradation. BRCA proteins have emerged as key stabilizing factors for the maintenance of replication forks following replication stress. Here the authors describe how reversed replication forks are degraded in the absence of BRCA2, and a MUS81 and POLD3-dependent mechanism of rescue following the withdrawal of genotoxic agent.